False Positive B-Cells Crossmatch after Prior Rituximab Exposure of the Kidney Donor. (28th April 2016) - Desoutter, Judith; Apithy, Marie-Joëlle; Bartczak, Ségolène; Guillaume, Nicolas
Abstract : Crossmatching is essential prior to kidney transplantation to confirm compatibility between the donor and the recipient, particularly to prevent acute antibody-mediated rejection. An unexpected positive crossmatch may be obtained in recipients with an autoimmune disease or preexisting antibodies not detected by single-antigen bead array due to complement interference or who have been previously treated by desensitization protocols such as rituximab, antithymocyte globulin, or intravenous immunoglobulins. We report donor and recipient investigations that revealed unexpected positive B-cells crossmatch, probably due to donor cells, as the donor had received rituximab therapy shortly before organ harvesting, in a context of severe idiopathic thrombocytopenic purpura. We consequently detected unexpected Class II IgG complement-dependent cytotoxicity for all sera tested. Other laboratory investigations failed to elucidate the reasons for this recipient-related positivity.